Analysis by multiple criteria for the definition of environmental fragility levels – A case study: watershed of Cará-Cará River, Ponta Grossa/PR - Marcos Antonio Miara; Chisato Oka-Fiori (Revista Raega: O Espaço Geográfico em Análise, 2007)
The GIS (Geographical Information Systems), as a tool for theenvironmental analyses of specific modules, makes possiblethe use of different sources of information simultaneously. Inorder to exploit this characteristic, the present research applieda Multi criteria evaluation (MCE), using also the AHP (AnalyticHierarchy Process) for the identification of differentiated levelsof environmental fragility from the definition of weights for theconsidered physical variables. The work has used the Cará-Cará River watershed, Ponta Grossa/PR, as its study area.The results have shown a five-class variation of environmentalfragility, which have been correlated witch the reality, givingsupport to a positive evaluation of the methods which wereused.